KEMAMPUAN PENALARAN INDUKTIF MATEMATIS DAN RASA INGIN TAHU SISWA MUHAMMADIYAH SOKARAJA - Dian Alif Fitriana (Department of Mathematics Education, Universitas Muhammadiyah Purwokerto, Indonesia, 2017)
This study aimed to describe the inductive reasoning mathematically ability and curiosity of8th grade students of SMP Muhammadiyah Sokaraja. This research was descriptivequalitative. Sampling using purposive sampling. In this study, students are grouped into threegroups namely the achievement of students with low, medium and high are determined basedon the value of UTS the second semester of the school year of 2014/2015 in class VIII C SMPMuhammadiyah Sokaraja. Each group selected three students for the purposes of theinterview. The method of collecting data in this study using tests, interviews, questionnairesand documentation. The results obtained: 1) Reasoning Inductive Mathematical: Studentswith low achievement has not been able to examine the patterns and structures to findregularities of patterns, formulate generalizations and allegations of regularities were found,and has not been able to draw conclusions, compile evidence and reasoning / proof of thetruth of the solution. Students with moderate achievement simply can not draw conclusions,compile evidence and give reasons / evidence of the truth of the solution. While students withhigh achievement already meet the three indicators of inductive reasoning mathematically. 2)Curiosity: Students with low achievement is already showing early signs of curiosity towardsmathematics. While students with moderate and high achievement already showing curiosity /interest towards mathematics.KEY WORDS: Inductive Reasoning Mathematically, Curiosity